MnO Nanocrystals: A Platform for Integration of MRI and Genuine Autophagy Induction for Chemotherapy. (26th October 2012) - Lu, Yang; Zhang, Li; Li, Jing; Su, Yu‐De; Liu, Yun; Xu, Yun‐Jun; Dong, Liang; Gao, Huai‐Ling; Lin, Jun; Man, Na; Wei, Peng‐Fei; Xu, Wei‐Ping; et al.
Abstract Herein, a kind of novel monocomponent hydrophilic and paramagnetic manganese(II) oxide nanocrystal is prepared in polar solution by a one‐pot microwave‐assisted synthesis. This kind of nanocrystal can be taken up efficiently to serve as an excellent T1 magnetic resonance imaging (MRI) contrast agent with an enhanced r1 value of 0.81 mM−1 s−1. The key to the success of this method is that no additional capping agents are required for coating onto the surface via ligand exchange, facilitating research of their intrinsic biological activities. Furthermore, multiple lines of convincing evidence are presented to prove that MnO nanocrystals (NCs) elicit p53‐activation‐independent and authentic functional autophagy via inducing autophagosome formation. Notably, there are very few reports so far of the autophagy phenomenon induced by magnetic nanocrystals. Moreover, these results offer an indication for cancer therapy that MnO NCs combined with doxorubicin at a nontoxic concentration can have a definite synergistic effect, which is mediated through the genuine autophagy induction, on killing cancer cells in vitro and in vivo.